Ligand‐Dependent Chemoselectivity in Gold‐Catalyzed Reactions between Anthranils and Diynamides. Formation of Spiro Azacyclic Compounds versus 1‐Imino‐1H‐Indene‐3‐Carboximidamides - Satish Bhausaheb Dawange; Rai‐Shung Liu (ChemistryEurope)
Gold‐catalyzed reactions between anthranils and diynamides have been investigated, and their reaction chemoselectivity relies on the types of gold catalysts. With the same anthranil/diynamide mixtures, the use of PPh3AuCl/AgNTf2 leads to formation of spiro azacyclic compounds, whereas P(t‐Bu)2(o‐biphenyl)AuCl/AgNTf2 preferably yields 1‐imino‐1H‐indene‐3‐carboximidamides instead. In the PPh3AuCl/AgNTf2 system, an indole intermediate at low temperature for X‐ray diffraction study is isolated; this isolable indole species requires anthranil and gold catalyst for efficient formation of spiro azacyclic products. In the case of P(t‐Bu)2(o‐biphenyl)AuCl/AgNTf2, the mechanism of its resulting 1‐imino‐1H‐indene‐3‐carboximidamides is postulated based on literature reports.